The Rising Vulnerability of Indonesian Language Culture: Analyzing the Encoded Politeness in the Use of Plural Second-Person Pronouns - ., Ermitati; Fajrin R, Hasina; Biopsi Puji Hastuti, Heksa; Saptarini, Tri; Agus Kurnianto, Ery (KnE Social Sciences, 2023)
This article explored the use of Indonesian pronouns by young people in Indonesia. The way in which they use pronouns erodes Indonesian culture encoded in Indonesian pronouns. They use the pronouns kamu (you, second-person singular pronoun), kalian (you, second-person plural pronoun), kita (we (you and me), first-person plural pronoun), and kami (we (not including you), first-person plural pronoun) that do not comply with Indonesian grammar. The data was collected by observing language used among the younger generation online and in everyday speech. The data was analyzed using a book on Indonesian grammar by A. M. Moeliono et al. The results discovered that Indonesian pronouns express politeness, particularly in the use of kamu and kalian (you, second-person plural pronouns), and the differences between first-person plural pronouns kita (we (you and me), first-person plural pronoun), and kami (we (not including you), first-person plural pronoun). Keywords: Indonesian Language, Pronoun, Culture, Politeness